Increasing Metacognitive Capacity by Disrupting Implicit Leader Prototypes. Issue 159 (1st June 2018) - Brooks, Ben; Chapman, Natasha H.
Abstract: Metacognitive capacity (i.e., thinking about how one thinks) is a fundamental component of critical leadership development. This chapter offers practical insights on how to leverage the exploration of implicit leader prototypes as a powerful vehicle for building metacognitive capacity.